PENGARUH MODAL SENDIRI DAN MODAL LUAR TERHADAP SISA HASIL USAHA MELALUI VOLUME USAHA PADA KOPERASI - Rahayu, Ni Made Supianti; Ayuningsasi, A.A Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 7, Juli 2018 (pp. 1352-1586), 2018)
The purpose of this research is to know the influence of own capital and external capital to business volume, influence of own capital, external capital and business volume to the rest of business result and to know the role of business volume in mediating the influence of own capital and external capital to SHU KSP in Denpasar City. This research was conducted on Savings and Loans Cooperative (KSP) in Denpasar City with total sample of 37 KSP. Data used is secondary from the Office of Cooperatives and SMEs of Denpasar. Technique of data analysis using path analysis. The results showed that the capital itself had a positive and significant effect on business volume in KSP in Denpasar City. Own capital positively and significantly influence SHU on KSP in Denpasar City. Outside capital positively and significantly influence SHU on KSP in Denpasar City. The volume of business has a positive and significant impact on SHU in KSP Denpasar. The volume of business can not mediate the influence of its own capital and external capital against SHU KSP in Denpasar City.